Respon Pertumbuhan dan Hasil pada Tanaman Bayam (Amaranthus sp) terhadap Biofortifikasi Unsur Hara Kalsium (Ca) dan Besi (Fe) dengan Sistem Hidroponik DFT (Deep Flow Technique) - Hasmeda M; IY Sari; Munandar Munandar; M Ammar; F Gustiar (Seminar Nasional Lahan Suboptimal, 2021)
Hasmeda M, Sari IY, Munandar M, Ammar M, Gustiar F. 2021. Growth response and yield of spinach (Amaranthus sp) on biofortification of calsium (Ca) and iron (Fe) with DFT (Deep Flow Technique) system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 721-733. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research was conducted to know the dose of calcium (Ca) and Ferro (Fe) which were the best factor in the increase of plant nutrient which did not disturb the growth and production of Amaranthus sp. by using hydroponic DFT (Deep Flow Technique). This research was conducted at Hydroponic laboratory Agronomy study program Faculty of Agriculture Sriwijaya University which was conducted from November 2020 until April 2021. This research used Amaranthus seed brand “Panah Merah”. The Randomized Block Design with 8 treatments and three replications were used. They were: CFo = AB, C1=200 ppm, C2=400 ppm C3-600 ppm, F1=5 ppm, F2=7.5 ppm and F3=10 ppm. Diversity Analysis used ANOVA and BNT 5%. Parameters being observed were plant height (cm), Number of leaves, leaves greenest level, leaf area (cm2), root volume (ml3), fresh plant weight (g), dry plant weight (g), Calcium concentration (Ca) and Fe concentration in leaves. Research results showed that the increases of Ca and Fe concentration occurred along with the increase of hydroponic solution. The increase of Ca 600 ppm did not inhibit plant growth and the increase of Fe 5 ppm was the maximum concentration which not inhibit the growth of Amaranthus and gave good impacts and optimal plant growth.